2020
DOI: 10.3389/fnins.2020.571479
|View full text |Cite
|
Sign up to set email alerts
|

Optimized OPA1 Isoforms 1 and 7 Provide Therapeutic Benefit in Models of Mitochondrial Dysfunction

Abstract: Optic Atrophy 1 (OPA1) is a mitochondrially targeted GTPase that plays a pivotal role in mitochondrial health, with mutations causing severe mitochondrial dysfunction and typically associated with Dominant Optic Atrophy (DOA), a progressive blinding disease involving retinal ganglion cell loss and optic nerve damage. In the current study, we investigate the use of codon-optimized versions of OPA1 isoform 1 and 7 as potential therapeutic interventions in a range of in vitro and in vivo models of mitochondrial d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 69 publications
0
12
0
Order By: Relevance
“…Activation of OMA1 in mouse heart leads to mitochondrial fragmentation and disrupted metabolism, causing dilated cardiomyopathy and heart failure (Wai et al, 2015), while genetic ablation of OMA1 prevents OPA1 cleavage, delaying neuronal apoptosis in a murine neurodegeneration model (Korwitz et al, 2016), as well as mouse models of heart failure (Acin-Perez et al, 2018). Consistent with this, OMA1 silencing confers increased cell proliferation and migration in patient-derived metastatic cancer cells (Daverey et al, 2019), while adenoviral delivery of OPA1 rescues mitochondrial dysfunction in in vitro models (Maloney et al, 2020). Taken together, these findings suggest that OMA1's role in controlling stress-sensitive OPA1 cleavage has crucial importance to cellular fate through modulation of apoptosis.…”
Section: Oma1 Opa1 and Cellular Apoptosismentioning
confidence: 73%
“…Activation of OMA1 in mouse heart leads to mitochondrial fragmentation and disrupted metabolism, causing dilated cardiomyopathy and heart failure (Wai et al, 2015), while genetic ablation of OMA1 prevents OPA1 cleavage, delaying neuronal apoptosis in a murine neurodegeneration model (Korwitz et al, 2016), as well as mouse models of heart failure (Acin-Perez et al, 2018). Consistent with this, OMA1 silencing confers increased cell proliferation and migration in patient-derived metastatic cancer cells (Daverey et al, 2019), while adenoviral delivery of OPA1 rescues mitochondrial dysfunction in in vitro models (Maloney et al, 2020). Taken together, these findings suggest that OMA1's role in controlling stress-sensitive OPA1 cleavage has crucial importance to cellular fate through modulation of apoptosis.…”
Section: Oma1 Opa1 and Cellular Apoptosismentioning
confidence: 73%
“…Rotenone is a lipophilic, naturally occurring compound acting as a strong inhibitor of complex I of the mitochondrial respiratory chain [ 122 ]. Using the murine model of rotenone-induced optic neuropathy, Maloney et al the reported therapeutic benefit of OPA1 isoform 1 and 7 delivered by AAV-2 via IVT route [ 123 ].…”
Section: Gt Of Diseases Caused By Ndna Mutationsmentioning
confidence: 99%
“…OPA1 plays essential roles in mitochondria, including remodeling cristae morphology, inner mitochondrial membrane fusion, efficiency of oxidative phosphorylation, and mitochondrial genome maintenance. Under normal conditions, there is a stoichiometric balance between L-Opa1 and S-Opa1, and each function is performed by specific isoforms [6].…”
Section: Introductionmentioning
confidence: 99%